Nematoda Entomopatogen Heterorhabditis Isolat Lokal Madura Sebagai Pengendalian Hayati Hama Penting Tanaman Hortikultura yang Ramah pada Lingkungan - - Sucipto (Agrovigor, 2009)
The purpose of this research to determine the potential of Heterorhabditis spp an Entomopatogen Nematoda biological agents as alternative control of pest crop which is environmentally friendly. which has a simple life cycle and have the stadia development of eggs, juvenile, and adult. In supporting its effectiveness, nematodes bacteria entomopatogen need simbion with bacteria that Photorhabdus. Heterorhabditis advantages are: a broad host range, rapid insect killing (48 hours), can be cultured in artificial media, durable infection stadia, does not cause resistance to the host and really safe for the environment